Die Formeln von Liouville und Spitzenformen, die von verallgemeinerten binären Thetareihen erzeugt sind - Kogan, L. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. А. Коган. Формулы Лиувилля и параболические формы, порожденные обобщенными бинарными тэта-рядами L. Koganas. Liuvilio formulės ir parabolinės formos, gautos iš apibendrintų binarinių teta-eilučių